ChemInform Abstract: Synthesis of Li3V2(PO4)3/C for Use as the Cathode Material in Lithium Ion Batteries Using Polyvinylidene Fluoride as the Source of Carbon. Issue 27 (18th June 2015) - Li, Lingfang; Fan, Changling; Zhang, Xiang; Zeng, Taotao; Zhang, Weihua; Han, Shaochang
Abstract The cathode material of title is prepared by a hybrid sol—gel method from an aqueous 1:3:1.5:3:0.1 mixture of V2O5, Li2CO3, NH4H2PO4, H2C2O4, and cetyltrimethyl ammonium bromide using polyvinylidene fluoride as the carbon source (sintering at 700 °C for 10 h under Ar).